PERAN SEKOLAH DALAM MENINGKATKAN KESADARAN HUKUM BERLALU LINTAS SISWA SMA NEGERI 3 CIREBON - Hasibuan, Jimmy Pranata (Civic Education Program, Universitas Negeri Semarang, 2017)
The number of transport annually has increased in Indonesia, especially in road transport, but it is also the level of traffic violations in the city of Cirebon high, according to data of the Directorate of Traffic Police Department Republic of Indonesia West Java Cirebon City resort number of traffic violations totaled 25371 traffic violation (Data: Traffic Police Resort Cirebon City, 2014), and based on an initial survey in SMAN 3 Cirebon as a formal educational institution that has a policy regarding motor vehicle parking system students who drive to school. Formulation of the problem in this research are: 1) How does the role of schools in raising awareness of road traffic in SMA Negeri 3 Cirebon, 2) How is the impact of school policies regarding motor vehicle parking system in raising awareness of traffic laws SMA Negeri 3 Cirebon. Qualitative research approach. Location study in SMA Negeri 3 Cirebon. Data collection techniques by observation, interview and documentation. Triangulation techniques through interviews and observations. Results of this study of the role of school SMA Negeri 3 Cirebon through activities such Intrakurikeler exists only in learning PPKN, and BK, and through extracurricular activities organized dissemination activities about the traffic, the distribution of helmets to students in collaboration with the department of transportation, driver's license held school in cooperation with the police, every morning in front of the school there are police who helped ferrying students, teachers, and employees of SMA Negeri 3 Cirebon and parking policy SMA Negeri 3 Cirebon. The impact of school policies regarding parking system in raising awareness of road traffic law only in terms of knowledge, and attitude